Liebenthal, Rush County - Miller, Chad (Kansas State University, The Chapman Center for Rural Studies, 2010)
Jacob Herrman founded the land in Rush County, Kansas that came to be known as Liebenthal. The village of Liebenthal still stands today as the proud religious community ithas always been, but it has gotten considerably smaller. It is most likely that the town has remained because its main street is U.S. Highway 183. This road is one of the more frequently traveled U.S. Highways, as it runs from Canada to Mexico.
Chad Miller, “Liebenthal, Rush County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/33.
Keywords: Big Timber Creek; Fr. Rudolph Stollenwerk; Homestead Act; Jacob Herrman; Liebenthal; Rush County